The Finite Element Method and Applications in Engineering Using ANSYS® - Madenci, Erdogan; Guven, Ibrahim (Springer US : Imprint: Springer, 2006)
The Finite Element Method and Applications with ANSYS® provides the reader with theoretical and practical knowledge of the finite element method and with the skills required to analyze engineering problems with ANSYS®, a commercially available FEA program. This self-contained, introductory text minimizes the need for additional reference material, covering the fundamental topics in finite element methods, as well as advanced topics concerning modeling and analysis with ANSYS®. These subjects are introduced through extensive examples from various engineering disciplines and are presented in a clear, step-by-step fashion. The book focuses on the use of ANSYS® through both the Graphics User Interface (GUI) and the ANSYS® Parametric Design Language (APDL). This volume addresses these specific areas: An introduction to FEM Fundamentals and analysis capabilities of ANSYS®, with practical modeling considerations Fundamentals of discretization and approximation functions Modeling techniques and details of mesh generation in ANSYS® Creating solutions and reviewing results Finite element equations based on the method of weighted residuals and on the principle of minimum potential energy The use of commands and APDL and the development of macro files Example problems and solutions corresponding to linear structural analysis Example problems and solutions related to heat transfer and moisture diffusion Nonlinear structural problems Advanced subjects such as submodeling, substructuring, interaction with external files, and modification of ANSYS®-GUI Additional materials for this book, including the "input" files for the example problems, as well as the colored figures and screen shots, allowing them to be regenerated on the reader's own computer, may be downloaded from http://extras.springer.com. Students, researchers, and practicing engineers will find this an essential reference for use in predicting and simulating the physical behavior of complex engineering systems using ANSYS®.  .